ANALISIS KANDASNYA TONGKANG XYZ DENGAN PANJANG 76,20 METER DI PERAIRAN LAMONGAN DAN PROSES PERBAIKANNYA - Tarisa Pebriyanti, (2023)
One type of ship accident that often occurs in Indonesia is a ship aground. Ship accidents that occur will have an impact and loss. This writing aims to find out the causes, stability conditions, as well as the evacuation and repair process for the XYZ Barge which ran aground in Lamongan waters in early January 2022. Data collection was carried out using a qualitative descriptive method based on direct observations at the shipyard and interviews with the team members involved. XYZ barge with the Banjarmasin-Batang shipping route switched routes to Lamongan to carry out repairs due to a torn bottom on the FP-tank 2 section and extending on the left side of the FP-tank 8 while transferring cargo from another barge in Karimun Waters. While waiting for the docking queue, Barge XYZ ran aground in Lamongan Waters due to bad weather and disturbed stability. Based on stability calculations on Maxsurf Stability with IMO A.749 and IMO MSC.267(85) criteria for the pontoon category, it was found that the XYZ Barge in a fully loaded condition met all the criteria except for the maximum GZ angle which should have been > 25° but only 20° was obtained . The ability of the XYZ Barge to overcome leaks was only in tanks 4, 5, 6 and 9. The evacuation process was carried out based on the floating rescue method using wind pressure techniques. The repair process falls into the category of emergency docking.